Perkembangan Judi Online dan Dampaknya Terhadap Masyarakat Beserta Dalil dalam Al-Qur’an dan Hadits Tentang Perjudian - Nia Trisnawati; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The main issue of this journal discusses the impact of online gambling practices on society. The focus is to understand the negative consequences arising from online gambling and its implications for individuals and communities. The purpose of this study aims to analyze the impact of online gambling in the social context of society. The author wants to explain how online gambling practices affect individual well-being, social relationships, and family economic stability. Qualitative Method: The research approach used is a qualitative method. The author conducts analysis through content generated by the community related to online gambling, such as online forum discussions or relevant social media posts. The conclusion of the findings of this study reveals the significant negative impact of online gambling on society. Online gambling practices can cause destructive addiction, disrupt the financial stability of individuals and families, and damage social relationships. These negative influences require effective preventive measures,including education about the risks of gambling, strict regulations, and better supervision of online gambling platforms. In conclusion, this study emphasizes the importance of public awareness and responsive policies in addressing the negative impacts of online gambling on individuals and society as a whole.